Dissociative nature of C(sp2)–N(sp3) bonds of carbazole based materials via conical intersection: simple method to predict the exciton stability of host materials for blue OLEDs: a computational study. Issue 15 (1st April 2020) - Vijaya Sundar, J.; Rajakumar, B.
Abstract : C(sp 2 )–N(sp 3 ) fragmentation in OLED host materials is a fundamental property and it occurs through S0/S1 conical intersection. The kinetics of the degradation is controlled by excited state barrier height which is negatively correlated to HOMO–LUMO gap and thus provides information on the exciton stability of host materials in blue OLEDs. Abstract : In this work, the origin of the singlet and triplet exciton-induced degradation of host materials with C(sp 2 )–N(sp 3 ) bonds around nitrogen (carbazoles, acridines, etc. ), connecting donor and acceptor units, was unravelled using DFT and CASSCF methods. The results reveal that molecules (employed in OLEDs) with basic units containing C(sp 2 )–N(sp 3 ) bonds (nitrogen connected to carbon in a triangular fashion) have a natural tendency to fragment at the C–N bond through an S1/S0 conical intersection (CI). The calculation of barrier heights, to reach a dissociation point, indicates that degradation via triplet states is kinetically less feasible (Δ G T1–TS * > 25 kcal mol −1 ) compared to that via the first singlet excited state (Δ G S1–TS * ∼7–30 kcal mol −1 ). However, the long lifetime of triplets (as compared to singlets) aids in the reverse intersystem crossing from triplet to singlet state for subsequent degradation. From the results and inference, Δ G S1–TS * and Δ E S1–T1 are proposed to be the controlling factors for exciton-induced degradation of host materials with C(sp 2 )–N(sp 3 ) bonds. Furthermore, multiple functionalization of carbazole moieties reveals that polycyclic aromatic systems employed as acceptor units of host materials are best suited for PhOLEDs as they will increase their lifetime due to the larger Δ G S1–TS * and Δ E S1–T1 . For TADF-based devices, materials with fused ring systems (with N(sp 3 ) at the centre) in the donor unit are the most recommended ones based on the findings of this work, as they avoid the dissociative channel altogether. A negative linear correlation between Δ G S1–TS * and HOMO–LUMO gap is observed, which provides an indirect way to predict the kinetic stability of these materials in excitonic states. These initial results are promising for the future development of the QSAR-type approach for the smart design of host materials for long-life blue OLEDs.